2016
DOI: 10.1038/onc.2016.374
|View full text |Cite
|
Sign up to set email alerts
|

The hot-spot p53R172H mutant promotes formation of giant spermatogonia triggered by DNA damage

Abstract: Overexpression of mutant p53 is a common finding in most cancers but testicular tumours accumulate wild-type p53 (wtp53). In contrast to the accepted concept that p53 homozygous mutant mice do not accumulate mutant p53 in normal cells, our study on a mutant p53 mouse model of Li-Fraumeni syndrome harbouring the hot-spot p53R172H mutation described an elevated level of mutant p53 in non-cancerous mouse tissues. Here we use detailed immunohistochemical analysis to document the expression of p53R172H in mouse tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Accumulation of p53 in proliferative compartments but not in differentiated epithelia after bortezomib treatment suggested transcriptional control at the Trp53 locus as a possible reason. This hypothesis is supported by p53 reporter mice, where high levels of p53 protein and Trp53 transcripts were detected in spermatogonia .…”
Section: Intratumoural Heterogeneity Of P53 Expressionmentioning
confidence: 79%
See 1 more Smart Citation
“…Accumulation of p53 in proliferative compartments but not in differentiated epithelia after bortezomib treatment suggested transcriptional control at the Trp53 locus as a possible reason. This hypothesis is supported by p53 reporter mice, where high levels of p53 protein and Trp53 transcripts were detected in spermatogonia .…”
Section: Intratumoural Heterogeneity Of P53 Expressionmentioning
confidence: 79%
“…Expression of mutant p53R172H in the crypts of the small intestine and in the testis of adult LFS mice was found to be dependent on Trp53 allele copy number. Analysis of testes and small intestines from Trp53 +/− , Trp53 +/+ , Trp53 R172H/− and Trp53 R172H/R172H mice revealed higher p53 levels in tissues from homozygous than heterozygous mice and in homozygous mutant than homozygous WT mice [14,45]. As in normal intestinal crypts, intestinal adenomas show that the presence as well as the number of Trp53 R172H mutant alleles correlate with p53 IHC staining intensities relative to adenomas in Trp53 +/+ mice ( Figure 5A).…”
Section: Gene Dosagementioning
confidence: 99%
“…Stabilization of p53 by bortezomib in proliferative but not in differentiated epithelium reveals that the low levels or absence of p53 in differentiated epithelium is due to the transcriptional control of p53 RNA levels and this is further verified by p53 mRNA ISH. Support for such a strictly regulated transcriptional control of p53 has also come from studies using reporter genes knocked into the p53 locus (28). The rapid increase in protein levels in response to bortezomib in vivo suggested that the stabilization of previously translated protein was transiently matched by its active transcription, indicating that bortezomib can be used as a tool to verify the transcription levels of p53 and other proteasome-degraded proteins in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, low‐dose ionizing irradiation promotes the expression of 53BP1 in mouse spermatogonial stem cells, a deleterious event that presumably occurs in response to DNA double‐strand breaks (Le et al, ). Along the same lines, adult mouse testes express p53R172H (an indicator of mutations) in pre‐Sertoli cells, dark type A and type B spermatogonia, but absent in spermatocytes and spermatids (Xue et al, ). Finally, women and mice with BRCA1 mutations, show substantial DNA double‐strand breaks in their follicles as a functional BRCA1 gene is required to ensure genome integrity at different stages of ovum development (Titus et al, ).…”
Section: Discussionmentioning
confidence: 99%